(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
The possibility of attracting hydrometeorology students through the Student Scientific Society into the research and educational activities of the Russian State Hydrometeorological University is being considered. The activities of the divisions of the student society are analyzed and their long-term plans for development are noted. Current challenges facing the student scientific society have been identified.